Effect of Soil Inoculum Density of Fusarium oxysporum f. sp. vasinfectum Race 4 on Disease Development in Cotton - Hao, Jianjun J (Plant disease, 2009)
The effect of soil inoculum density (0 to 106 conidia/g of potting mix) of Fusarium oxysporum f. sp. vasinfectum race 4 on plant growth (weight, height, and number of nodes), Fusarium wilt symptoms, vascular discoloration, and number of CFU per gram of stem tissue was determined on five cotton cultivars grown in a greenhouse. In the susceptible cv. DP744, symptoms of wilt and reductions in plant growth occurred at inoculum levels of 103 conidia/g of potting mix and higher, whereas plant growth of the resistant Pima cv. Ph800 was not affected by any soil inoculum densities. Cvs. DP340, Ph72, and UltEF all responded similarly, with a relatively moderate negative growth response to soil inoculum densities generally beginning at 104 conidia/g of potting mix. F. oxysporum f. sp. vasinfectum race 4 was recovered from the stems of all cultivars by plating macerated stem tissue on a semiselective medium. There was a significant positive correlation between CFU and inoculum density above 104 conidia/g of potting mix for DP744 and UltEF. The fungus was recovered relatively infrequently from stems of Ph 800 plants inoculated with any inoculum density of F. oxysporum f. sp. vasinfectum. Fusarium wilt caused by F. oxysporum f. sp. vasinfectum race 4 is an inoculum density- dependent disease; the disease was generally mild and the fungus was rarely recovered from stems at inoculum levels less than 104 conidia/g of potting mix